Constructive and Simulated Annealing Algorithms for Hybrid Flow Shop Problems with Unrelated Parallel Machines - Jungwattanakit, Jitti; Reodecha, Manop; Chaovalitwongse, Paveena; Werner, Frank (Science & Technology Asia, 2015)
-